IMPLEMENTATION OF FUZZY LOGIC TO DETERMINE THE BEST EMPLOYEES - Maranata Pasaribu; Sartana Sartana; Sariadin Siallagan; Ratnawati Simbolon (Sean Institute, 2022)
Employees are people who are able to work and produce goods and services for their own needs and society. Every company really yearns for employees who are able to work professionally so that the company's targets can be met. How does the company motivate employees by rewarding the best employees so that employees are motivated to work. Selection of the best employees by setting 5 (five) criteria, namely: Discipline, Loyalty, Communication, Attendance and Problem Solving. The assessment is carried out by taking attendance data and observation visually. The Fuzzy Tsukamoto method is used to obtain accurate, relevant and quickly presented results. Developed an information system to be able to produce the right decision by processing 5 (five) criteria data whose processing combines all criteria values and high rated values as the BEST value.